2017
DOI: 10.1002/1873-3468.12861
|View full text |Cite
|
Sign up to set email alerts
|

NDRG2 acts as a PERK co‐factor to facilitate PERK branch and ERS‐induced cell death

Abstract: NDRG2, a newly identified tumor suppressor, is also responsive to various stresses, such as hypoxia and DNA damage. Here, we reported that in human hepatoma SK-Hep-1 and HepG2 cells, NDRG2 mRNA and protein levels were upregulated by different endoplasmic reticulum stress inducers including Tg, Tm, and DTT. Further, using NDRG2-overexpressing hepatoma cell lines and Ndrg2KO mice liver tissues, we found that, among the three branches of unfolded protein response signaling, NDRG2 facilitates protein kinase RNA-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…8. Glutamine withdrawal down-regulated the expression of most studied factors and these results completely agree with functional activity of ATF6, EIF2AK3/PERK, GLO1, BIRC5/survivin, and RAB5C proteins, which shown pro-proliferative effects [16][17][18][24][25][26][27][28][29][30][31][32].…”
Section: Fig 3 Effect Of Glutamine Deprivation On the Expression Lesupporting
confidence: 76%
See 1 more Smart Citation
“…8. Glutamine withdrawal down-regulated the expression of most studied factors and these results completely agree with functional activity of ATF6, EIF2AK3/PERK, GLO1, BIRC5/survivin, and RAB5C proteins, which shown pro-proliferative effects [16][17][18][24][25][26][27][28][29][30][31][32].…”
Section: Fig 3 Effect Of Glutamine Deprivation On the Expression Lesupporting
confidence: 76%
“…Furthermore, ATF6 activates stress responsible gene expressions and regulates cellular senescence, which is known as an anti-tumor barrier [5,26]. Eukaryotic translation initiation factor 2 alpha kinase 3 (EIF2AK3), which also known as PKR-like ER kinase (PERK), is an elF2alpha kinase that inhibits protein translation and is involved in control of cell proliferation and tumorigenesis, in mitochondrial function and apoptosis [27][28][29]. It is also an important signaling protein of endoplasmic reticulum stress signaling pathways [5].…”
Section: The Expression Of a Subset Of Genes Encoding Important Tumormentioning
confidence: 99%
“…Thus, overexpression of NDRG2 promotes ERS-induced apoptosis, while silencing or knockdown of NDRG2 does the opposite, both in cell lines and in vivo. These data suggest that NDRG2 is a novel ER stress-responsive protein and an important component of the UPRosome, acting as a PERK cofactor to facilitate PERK branch signaling and thereby contributing to ER stress-induced apoptosis [17]. Therefore, apart from its already established role, NDRG2 could be considered a component of the UPRosome and a key player in cell fate decisions during ER stress.…”
Section: The Finding Of Ndrg2mentioning
confidence: 90%
“…NDRG2 is a stress-responsive gene [1], and our laboratory recently reported that as such, NDRG2 is implicated in ER stress [17] in addition to the hypoxia and DNA damage response. Different ER stress inducers, including thapsigargin (Tg), tunicamycin (Tm) and dithiothreitol (DTT), can induce NDRG2 mRNA and protein expression in human hepatoma SK-Hep-1 and HepG2 cells.…”
Section: The Finding Of Ndrg2mentioning
confidence: 99%
“…Eukaryotic translation initiation factor 2 alpha kinase 3 (EIF2AK3), which also known as PKR-like ER kinase (PERK), is an elF2alpha kinase that inhibits protein translation and is involved in control of cell proliferation and tumorigenesis, in mitochondrial function and apoptosis [44] [45] [46]. Both activating transcription factor 6 and PKR-like ER kinase (PERK) are also important signaling proteins of endoplasmic reticulum stress pathway [5].…”
mentioning
confidence: 99%